PARADIGM SHIFT IN OPEN EDUCATION AND E-LEARNING RESOURCES AS TEACHING AND LEARNING IN PHILIPPINES - Mellissa Acosta (Jurnal Ilmiah Peuradeun, 2016)
Education has over the years moved from one stage of development to the other with its peculiarities and challenges. There have also been series of innovations, strategies and policies based on the changes in the society. Some of these changes require technological approach which usually poses challenges because the country, like other developing countries, is ill-prepared and unable to immediately address each educational challenge as it appears. The paradigm shift, general acceptance of the new move or model in global technological education, government policies and massive enrollment for e-education and e-learning by the learners, the attitudes of all concerned in the design and full implementation of ICT and e-learning policies in education should be sustained. Some of the students and even the teachers or facilitators may still prefer the print materials which may limit their knowledge, effectiveness and resourcefulness with time. As a result, there is an increase in demand for a more flexible and cost effective means of education through e-education, e-learning or open and distance learning. This has brought a paradigm shift on how people generally view the significance of e-learning for higher education in Philippines.